2004
DOI: 10.1177/0007650304262962
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Global and Institutional Antecedents of High-Level Corporate Environmental Performance

Abstract: Stories of firms that exceed local compliance requirements in their environmental performance appear routinely. However, we have limited theoretical explanations of what propels these firms to exceed compliance. Our theory suggests that global competitive and institutional pressures lead multinational firms to develop highlevel, environmental management systems (EMS) that make them more competitive. For economic and other reasons, select firms make the choice to rationalize their collective environmental perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 71 publications
5
129
0
3
Order By: Relevance
“…Along these lines, a recent line of research based on institutional theory (DiMaggio & Powell, 1983) suggests that the ecological environmental policies of firms are in large part constructed by the influences of their industry business environments (Hoffman, 1997;Sharfman, Shaft, & Tihanyi, 2004;Sharma, 2000). Thus, we reason that the influence of industry-level factors on CSP stem not only from exceptional occurrences such as high-profile scandals, but also from more mundane market, institutional and environmental forces that shape the industrial context.…”
Section: Firm Industry and Network Antecedents Of Corporate Social Permentioning
confidence: 91%
“…Along these lines, a recent line of research based on institutional theory (DiMaggio & Powell, 1983) suggests that the ecological environmental policies of firms are in large part constructed by the influences of their industry business environments (Hoffman, 1997;Sharfman, Shaft, & Tihanyi, 2004;Sharma, 2000). Thus, we reason that the influence of industry-level factors on CSP stem not only from exceptional occurrences such as high-profile scandals, but also from more mundane market, institutional and environmental forces that shape the industrial context.…”
Section: Firm Industry and Network Antecedents Of Corporate Social Permentioning
confidence: 91%
“…And similar to regulative institutions, normative institutions that relate to professional or industrial societies, and the norms and values at the cultural-cognitive level, differ across countries (Husted & Allen, 2006;Jamali & Neville, 2011). Internationalisation therefore increases the number and diversity of stakeholder pressures on the firm (Brammer, Pavelin, & Porter, 2006;Sharfman, Shaft, & Tihanyi, 2004), which can be argued to both positively and negatively affect corporate responsiveness (e.g. Kolk & Fortanier, 2013).…”
Section: Home-countries and Host-countriesmentioning
confidence: 99%
“…Previous studies have identified several drivers that motivate firms to meet or exceed compliance requirements in their environmental performance, which includes both internal capabilities and external opportunities and constraints [2,4,10]. The resource-based view suggests that internal resources classified as tangible, intangible, and personnel-based enable firms to implement environmental strategies and policies [10,19].…”
Section: The Drivers Of Environmental Performancementioning
confidence: 99%
“…As internal routines are established using accumulated tacit knowledge regarding environmental management, firm's environmental performance is likely to improve. In the case of multinational firms, the need to comply with varying environmental regulations worldwide often results in the establishment of environmental management systems [2]. Through such systems, multinational firms standardize their compliance procedures and seek to exceed the minimum environmental regulation standards of the countries that have the most stringent ones.…”
Section: The Drivers Of Environmental Performancementioning
confidence: 99%
See 1 more Smart Citation